2014
DOI: 10.1128/jvi.00028-14
|View full text |Cite
|
Sign up to set email alerts
|

NEMO Is Essential for Kaposi's Sarcoma-Associated Herpesvirus-Encoded vFLIP K13-Induced Gene Expression and Protection against Death Receptor-Induced Cell Death, and Its N-Terminal 251 Residues Are Sufficient for This Process

Abstract: IMPORTANCEKaposi's sarcoma-associated herpesvirus-encoded vFLIP K13 is believed to protect virally infected cells against death receptorinduced apoptosis and to activate the NF-B pathway by binding to adaptor protein NEMO/IKK␥. However, whether K13 can also induce gene expression independently of NEMO and the minimum region of NEMO that is sufficient for supporting K13-induced NF-B remain to be delineated. Furthermore, the contribution of NEMO and NF-B to the protective effect of K13 against death receptor-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…Such KSHV gene products would include vFLIP which can inhibit killing via Fas [27,28] and a second receptor mediated killing mechanism, TNF-α [29]. Consistent with these studies we found that expression of vFLIP in BJAB cells inhibited killing by anti-Fas antibody and TRAIL.…”
Section: Discussionsupporting
confidence: 86%
“…Such KSHV gene products would include vFLIP which can inhibit killing via Fas [27,28] and a second receptor mediated killing mechanism, TNF-α [29]. Consistent with these studies we found that expression of vFLIP in BJAB cells inhibited killing by anti-Fas antibody and TRAIL.…”
Section: Discussionsupporting
confidence: 86%
“…The HCMV UL36 gene encodes a multi-functional cell death suppressor, denoted viral inhibitor of caspase-8 activation (vICA) protein, which binds pro-caspase-8 and inhibits its activation by interference with its recruitment to DISC (McCormick et al, 2010). Similar vFLIPs from other herpesviruses have also been found, including herpesvirus saimiri protein ORF71 (Glykofrydes et al, 2000), equine herpesvirus 2 (EHV-2) protein E8 (Hu et al, 1997), and HHV-8 protein K13 (Tolani et al, 2014). …”
Section: Manipulation Of Apoptosis By Dna Virusesmentioning
confidence: 56%
“…KSHV encodes several anti-apoptosis factors, including vBcl-2 [74], vFLIP [75], vIAP [74], K1 [76,77], vIRF4 [78], LANA [79] and miR-K10a [80]. Together, these viral factors target both the extrinsic and intrinsic apoptosis pathways.…”
Section: Innate Immune Control Of Kshvmentioning
confidence: 99%